Exploring the Neuroprotective Potential of Icariin through Modulation of Neural Pathways in the Treatment of Neurological Diseases - Sharma, Sarthak; Mehan, Sidharth; Khan, Zuber; Tiwari, Aarti; Kumar, Aakash; Das Gupta, Ghanshyam; Narula, Acharan S.; Kalfin, Reni (Current Molecular Medicine, 2025)
Neuropathological diseases involve the death of neurons and the aggregation of proteins with altered properties in the brain. Proteins are used at the molecular level to categorize neurodegenerative disorders, emphasizing the importance of protein-processing mechanisms in their development. Natural herbal phytoconstituents, such as icariin, have addressed these neurological complications. Icariin, the principal compound in Epimedium, has been studied for its anti-neuroinflammatory, anti-oxidative, and antiapoptotic properties. Recent scientific investigations have shown that icariin exhibits promising therapeutic and preventive properties for mental and neurodegenerative disorders. In preclinical, icariin has been shown to inhibit amyloid development and reduce the expression of APP and BACE-1. Previous preclinical studies have demonstrated that icariin can regulate proinflammatory responses in neurological conditions like Parkinson's disease, depression, cerebral ischemia, ALS, and multiple sclerosis. Studies have shown that icariin possesses neuroprotective properties by modulating signaling pathways and crossing the blood-brain barrier, suggesting its potential to address various neurocomplications. This review aims to establish a foundation for future clinical investigations by examining the existing literature on icariin and exploring its potential therapeutic implications in treating neurodegenerative disorders and neuropsychiatric conditions. Future research may address numerous concerns and yield captivating findings with far-reaching implications for various aspects of icariin.
Keywords: Neuropathological diseases